PERLINDUNGAN HUKUM BAGI PENCIPTA LAGU TERHADAP LAGU CIPTAANNYA YANG DICOVER DI MEDIA SOSIAL - Oki Wija Dharmaja, I Dewa Nyoman; Sawitri, Dewa Ayu Dian (Kertha Negara : Journal Ilmu Hukum, 2025)
This research aims to examine the legal protection of songwriters' copyrights against the performance of cover songs by other musicians on social media platforms. In the digital era and with the increasing accessibility of information, musicians often upload cover song performances to various social media platforms to gain exposure and interact with fans. However, this activity has an impact on the copyrights of the original songwriters. The research also evaluates the policies that can be taken by relevant parties, including songwriters, cover musicians, and social media platforms themselves. Collaborative and innovative efforts are needed to find a balanced and fair solution for all parties involved. This research employs a normative approach to analyze the legal protection of cover songs performed by other musicians on social media platforms. Through a review of relevant literature and legislation, this research aims to identify the applicable legal framework in this context. The results of this research are expected to provide legal guidance and policy recommendations for relevant parties and to encourage further discussion on the dynamics of copyright in the context of music performance in the digital era.